The Political Economy of Sovereign Default - Sebastian Hohmann (Graduate Institute Publications, 2012)
What do self-interested governments' needs to maintain loyal groups of supporters imply for sovereign incentives to repay debt? Many sovereign defaults have occurred at relatively low levels of debt, while some highly indebted nations continue to honour their obligations. This poses a problem for traditional models of sovereign debt, which rely on the threat of economic sanctions to explain why and when a representative agent seeking to maximise social welfare would choose debt-repayment. The...